Laser-wound stimulated adventitious root formation of Rosa canina cuttings involves a complex response at plant hormonal and metabolic level - Morales Orellana, Raul Javier; Rath, Thomas; Druege, Uwe; Tandrón Moya, Yudelsy A.; von Wirén, Nicolaus; Winkelmann, Traud (Frontiers in Plant Science, 2024)
The presence of wounds in addition to the excision-induced wounds after severance from the stock plants is known to positively influence adventitious root formation of woody plant cuttings. Previous morphological studies highlighted laser wounding as a technique allowing to precisely control the decisive ablation depth. However, the biochemical processes involved in the response of rooting to the additional wounding remained unexplored. Therefore, the present study analyzed changes in the plant hormone and carbohydrate profiles in response to laser treatments of rose leafy single-node stem cuttings (Rosa canina 'Pfänder'). Concentrations of four groups of plant hormones and of carbohydrates were monitored in three different stem sections of the cutting base during the first eight days after excision of cuttings. Laser ablation caused an increase of vascular tissue dimension directly in the laser wound, and increased the quantity and quality of rooting compared to control cuttings. Biochemical results showed a clear early local rise of jasmonic acid (JA) directly in wounded areas after laser marking, as well as an increase in abscisic acid (ABA) that persisted for the subsequent days. Indole-3-acetic acid (IAA) levels were relatively high on day zero, but decreased thereafter. Interestingly, higher IAA levels were maintained in the stem section below the axillary bud compared with the opposite section. Laser-treated cuttings presented a clear increase in contents of IAA-amino acid conjugates (IAAGlu and IAAsp) and the oxidation product OxIAA. Differences in concentration of these IAA metabolites were related to the position of the laser wound relative to the axillary bud and leaf. Additionally, analyses indicate that laser treatments caused gradually increased levels of the cytokinin N6-isopentenyladenine (iP) in laser-treated zones, and of zeatin riboside specifically when the laser wound was placed on the leaf-bud side. Additional laser wounding reduced starch and sucrose levels in all wounded sections at the end of the evaluation period, independently of the wounding location. The results of this study indicate that presence of additional injured tissue triggers a complex biochemical adjustment at the base of the cutting responsible of inducing vascular tissue growth and capable of generating a positive response to adventitious root formation.